Optimization of the central thermal supply system as decision for the nonlinear network transporting problem - Levchuk A.P.; Botsula D.O.; Zagurskyi V.G.; Levchuk A.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2008)
Optimization of the central thermal supply system on an example proper to the area of municipal power economy is considered. A calculation model as decision of nonlinear network transporting problem is built. With its help optimum operating parameters integral expense description of network and economy which is here achieved are certain.